2017
DOI: 10.1002/cyto.b.21536
|View full text |Cite
|
Sign up to set email alerts
|

Standardized high‐sensitivity flow cytometry testing for paroxysmal nocturnal hemoglobinuria in children with acquired bone marrow failure disorders: A single center US study

Abstract: This is the first study to use a standardized high-sensitivity FLAER-based flow cytometry assay and the recommended cutoff of 0.01% to identify cells with PNH phenotype in pediatric patients with ABMFD in the United States. The identification of a PNH population in 46% of ABMFD supports the recommendation for high sensitivity PNH testing in children with these disorders. As a less sensitive assay using a cutoff of ≥ 1% PNH population would have missed 10 (27%) patients with minor PNH population or rare cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…The other main symptoms belonging to the classical clinical triad of PNH are bone marrow failure and thrombosis especially at unusual sites which is the single most frequent cause of death in PNH patients (3)(4)(5). Furthermore, flow cytometry is preferentially used for follow-up of PNH patients or patients that were suffering from other bone marrow failures like aplastic anemia or refractory cytopenia with unilineage dysplasia (RCUD) (3,8) as there is a well-known association between PNH and these other bone marrow diseases (10)(11)(12)(13)(14). Flow cytometry is the gold standard for identification and quantification of PNH phenotypes (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other main symptoms belonging to the classical clinical triad of PNH are bone marrow failure and thrombosis especially at unusual sites which is the single most frequent cause of death in PNH patients (3)(4)(5). Furthermore, flow cytometry is preferentially used for follow-up of PNH patients or patients that were suffering from other bone marrow failures like aplastic anemia or refractory cytopenia with unilineage dysplasia (RCUD) (3,8) as there is a well-known association between PNH and these other bone marrow diseases (10)(11)(12)(13)(14). Flow cytometry is the gold standard for identification and quantification of PNH phenotypes (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Using this method even small populations of GPI-deficient cells can be detected, which allows a quantitative assessment of the PNH population. Furthermore, flow cytometry is preferentially used for follow-up of PNH patients or patients that were suffering from other bone marrow failures like aplastic anemia or refractory cytopenia with unilineage dysplasia (RCUD) (3,8) as there is a well-known association between PNH and these other bone marrow diseases (10)(11)(12)(13)(14). Diverse markers and staining strategies for PNH testing are discussed in different manuscripts (7,9,11,(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency described in the literature is variable depending on the sensitivity of the assay and the age group included, and it has varied from 12.9% to 48.8%. 4,5,[13][14][15][16] In a study by Sreedharanunni et al 4 , PNH clone of more than 1% was found in 12.9% (9/70) of paediatric AA cases. In another study of 103 paediatric patients of age less than 18 years of age, PNHpositive cells were found in 21.4% children using high sensitivity non-FLAER-based analysis.…”
Section: Discussionmentioning
confidence: 95%
“…This finding was in concordance with other previous studies. 5,13,14 To conclude, this was the largest single centre analysis of FLAER-based PNH screening of paediatric AA cases. A high prevalence rate (33.2%) of PNH clones was noted in these patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation